2017
DOI: 10.5114/jcb.2017.69237
|View full text |Cite
|
Sign up to set email alerts
|

Assessing dose contribution to pelvic lymph nodes in intracavitary brachytherapy for cervical cancer

Abstract: PurposeIn radical radiotherapy for cervical cancer, high-dose-rate (HDR) brachytherapy is commonly used after external beam radiation therapy (EBRT) to deliver a cumulative EQD2 of 80 to 90 Gy to the primary tumor. However, there is less certainty regarding brachytherapy dose contribution to the pelvic lymph nodes. This poses a challenge as to how high a preceding EBRT dose should be prescribed to gross nodal disease, in order to achieve a cumulative tumoricidal effect. Hence, this study aims to quantify brach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Similar studies have been done by Chua et al [8], Lee et al [11], Lee Y et al [12] and Matsukawa et al [13], where they did CT based planning but prescribed to point A.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similar studies have been done by Chua et al [8], Lee et al [11], Lee Y et al [12] and Matsukawa et al [13], where they did CT based planning but prescribed to point A.…”
Section: Discussionsupporting
confidence: 67%
“…With a brachytherapy dose of 5 Gy to point A, the mean EQD2 doses received by the EI, II and OB groups were 0.71, 1.04, and 1.27 Gy, respectively. With a brachytherapy dose of 6 Gy, the mean EQD2 doses received by the EI, II, and OB groups were 1.08, 1.49, and 1.77 Gy, respectively [8]. In our study, using volume based prescription to a dose of 6.5 Gy per fraction, the median EQD2 ranged between 3.92-5 Gy for point B, 1.78-2.16 Gy for the ELN groups, 2.88-3.56 Gy for the ILN groups and 4-5.2 Gy for the OBT groups across the three arms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average dose delivered to the external iliac, internal iliac and obturator lymph nodes was 4 Gy, 5.09 Gy and 5.47 Gy, respectively. In a similar study by Ying Chua et al, 21 the mean absolute dose received by the external iliac, internal iliac and the obturator lymph nodes was 0.79 Gy, 1.12 and 1.34 Gy, respectively with a point A dose of 5 Gy and 1.16 Gy, 1.56 Gy and 1.80 Gy, respectively, with a point A dose of 6 Gy.…”
Section: Discussionmentioning
confidence: 63%
“…quantified the brachytherapy dose contribution to pelvic node groups using the Manchester method. They indicated that the mean cumulative EQD 2 doses to the external iliac, the internal iliac, and the obturator nodes were 4.30 Gy, 5.95 Gy, and 7.09 Gy, respectively, in patients who received 6 Gy × 4 fractions [25]. Thus, the brachytherapy dose was reported to make a significant contribution in these studies, and the accurate evaluation of the dose delivered to the pelvic lymph nodes by brachytherapy is essential.…”
Section: Discussionmentioning
confidence: 99%